How External Environment Changes Personality of People? - Sri Pawan Kumar Pandey (JOURNAL OF MANAGEMENT, SCIENCES, OPERATION & STRATEGIES, 2023)
In this paper I am mentioning an incidence that happened with me in an organization. By the mode of that incidence I want to explain that external environment plays a great role in shaping up our language skills and professional personality. External environment has got the power to influence the mindset, physical appearance, behavioral etiquettes and mental make-up of professionals who are working in different corporate environments in the country. This research paper is explaining one such incidence that I saw during my tenure as Polycom Videoconferencing Engineer for my Maruti Suzuki India Limited, Vasant Kunj,New Delhi, on behalf of my parent organization, IT Source Technologies, Gurgaon, Haryana..